Islet-Derived eATP Fuels Autoreactive CD8+ T Cells and Facilitates the Onset of Type 1 Diabetes - Tezza, Sara; Ben Nasr, Moufida; D’Addio, Francesca; Vergani, Andrea; Usuelli, Vera; Falzoni, Simonetta; Bassi, Roberto; Dellepiane, Sergio; Fotino, Carmen; Rossi, Chiara; Maestroni, Anna; Solini, Anna; et al. (Diabetes (New York, N.Y.), 2018)
Extracellular ATP (eATP) activates T cells by engaging the P2X7R receptor. We identified two loss-of-function P2X7R mutations that are protective against type 1 diabetes (T1D) and thus hypothesized that eATP/P2X7R signaling may represent an early step in T1D onset. Specifically, we observed that in patients with newly diagnosed T1D, P2X7R is upregulated on CD8+ effector T cells in comparison with healthy control subjects. eATP is released at high levels by human/murine islets in vitro in high-glucose/inflammatory conditions, thus upregulating P2X7R on CD8+ T cells in vitro. P2X7R blockade with oxidized ATP reduces the CD8+ T cell–mediated autoimmune response in vitro and delays diabetes onset in NOD mice. Autoreactive CD8+ T-cell activation is highly dependent upon eATP/P2X7R-mediated priming, while a novel sP2X7R recombinant protein abrogates changes in metabolism and the autoimmune response associated with CD8+ T cells. eATP/P2X7R signaling facilitates the onset of autoimmune T1D by fueling autoreactive CD8+ cells and therefore represents a novel targeted therapeutic for the disorder.